(untitled) (Global Journal of Management and Business Research, 2014)
Mobile telecom sector in Bangladesh has reached at a desired level. Competition in this industry intensifies the urgency of making customer satisfied for corporate profitability and survival in a competitive marketplace. This study is conducted on 140 Grameenphone (GP) users in Bangladesh. The Study reveals that customer extended in respect of age, income, education. Major part of customers uses value added and multiple operators’ service; therefore study indicates the urgency of customer satisfaction. The correlation with the factors leading to customer satisfaction found to be positive except network & signal coverage. Finally, multiple regression analysis indicates that GP’s service innovativeness, service reliability, service competitiveness, customer demand fulfillment to be found significant and GP’s service consistency, network & signal coverage, pricing policy, quality of the offering, value added service, contribution to society and brand value to be found insignificant for affecting customer satisfaction. On the basis of these findings; study concludes that customer satisfaction is a dynamic phenomenon. Maintaining desired level of customer satisfaction requires corporate proactive responsiveness in accessing, building & retaining satisfied customers for sustainable competitive advantages in market place.